ACCUMULATION OF SCIENTIFIC KNOWLEDGE ON THE HYDROPOWER RESOURCES OF THE NORTH CAUCASUS AND FIRST STEPS TOWARDS THEIR IMPLEMENTATION - R. S. GURTUEV; P. A. KUZ’MINOV (Кавказология)
The Russian State Electrification Plan, which is celebrating its centenary this year, has become the basis for Russia's fundamental economic modernization, which has been carried out in an extremely short period of time by historical standards. Today, when many researchers are looking for the true authors of the country's electrification plans respectively assessing the contribution of the Tsarist and Bolshevik governments to its preparation, and often giving these disputes an ideological coloring; the authors of this article prove the absolute continuity of electrification plans using the example of the Caucasus region. Moreover, sources show that the creators of almost all the technical projects and plans – both in Tsarist and Soviet times – were the same people – major scientists, energy engineers, who were actively involved in the development of the GOELRO plan.